A COMBINATION PROPHETIC LEADERSHIP (LI) WITH KI HAJAR DEWANTARA LEADERSHIP (L2) TO INCREASE BUREAUCRATIC REFORMATION RESULTS - Dwi Nugroho Hidayanto (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The combined of prophetic leadership and trilogy leadership concepts called as neo-prophetic leadership. The neo-prophetic leadership covers prophets characteristics and Dewantara’s teachings. The combining two leaderships models -then become L1L2- is believed able to increase result of bureaucratic reformation. The combination referred to descriptive and prescriptive theories which were developed from theoretical and empirical perspectives. In this writing, L1 as a symbol of Prophetic Leadership, and L2 as a symbol of Dewantara’s Leadership which he is a bringer of leadership trilogy teachings. This is a leadership prescription that derived from eternal universal values -prophetic- while still maintaining local wisdom values -trilogy- which its effectiveness detail explained descriptively. L1L2 need to be tested by leaders and placed the organization as a laboratory to try-out it.